Conflict management for security professionals - Tufano, Andrew A. (Butterworth-Heinemann, 2014)
Effectively resolving conflict prevents violence, reduces incidents, improves productivity, and contributes to the overall health of an organization. Unlike the traditionally reactive law enforcement approach to resolving conflict, Conflict Management for Security Professionals provides a proven, reliable, business-focused approach that teaches security personnel to diffuse situations before they escalate when dealing with uncooperative, dangerous, or violent individuals. Covering everything from policies and procedures to security tactics and business impact, Conflict Management for Security Professionals uniquely addresses conflict resolution from a security perspective for managers, policy makers, security officials, or anyone else who interacts with people every day. This book helps organizations create and maintain safe environments without interfering with their ability to remain profitable, competitive, and relevant. Comprehensive and systematic conflict management and resolution program geared specifically for the needs of security managers, supervisors, and officers. Incorporates classroom and field-tested conflict resolution concepts, models, and approaches. Addresses everything from policies and programs to tactics for a wide variety of stakeholders in any private or public organization.